(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Garcinia gummi-gutta is commercially an important plant as its leaves and fruits contain valuable chemical components and are used for various ailments and treatments. Even though, there are minimum reports that have been seen in their exploration of this plant in the field of nanotechnology. So the present study deals with the synthesis of silver nanoparticles from the aqueous and ethanol leaf extracts of G. gummi-gutta and screening its antimicrobial and anticancer properties. Green synthesized silver nanoparticles was characterized by UV-visible (UV-vis) spectroscopy, transmission electron microscopy (TEM), fourier transforms infrared spectroscopy (FTIR) and X-ray diffraction (XRD) studies. In UV-vis spectroscopy, the surface plasmon resonance (SPR) spectrum of silver nanoparticles produced prominent peaks at 365 and 363 nm in aqueous and ethanol leaf extracts of G. gummi-gutta, respectively. Scanning electron microscopy (SEM) and XRD studies showed that the biosynthesized silver nanoparticles from aqueous and ethanol extracts of G. gummi-gutta leaves are spherical and crystalline in nature with an average size of 25 and 23 nm. FTIR spectroscopy reveals that the functional groups are responsible for the synthesis and stabilization of silver nanoparticles. The biosynthesized silver nanoparticles from both plant extracts have remarkable antibacterial and anticancer properties. Through these studies, it was found that silver nanoparticles from the ethanol leaf extract of G. gummi-gutta is more potential than silver nanoparticles from the aqueous leaf extract of G. gummi-gutta. So the present study is a novel attempt to synthesize the silver nanoparticles from this plant and elucidate its antimicrobial and anticancer potential.